Case report: Spontaneous pneumothorax in resolved, uncomplicated COVID-19 Pneumonia-A literature review. (2020) - Dennison, Jennifer; Carlson, Samuel; Faehling, Shannon; Lieb, Margaret; Mubarik, Ateeq
Abstract: As the global COVID-19 pandemic has progressed, awareness of uncommon presentations and complications has increased. The actual incidence of spontaneous pneumothorax was found to be 0.66%, or six patients out of 902 who tested positive in recently published literature of 3368 patients (Zantah M, Dominguez Castillo E, Townsend R, Dikengil F, Criner GJ. Pneumothorax in COVID-19 disease-incidence and clinical characteristics. Respir Res. 2020 Sep 16; 21 (1):236.). Of those six patients, only two (0.22%) were not associated with mechanical ventilation barotrauma or comorbid lung disease such as COPD. Here, we present a spontaneous pneumothorax and pneumomediastinum in a patient four days after he had been discharged from hospitalization due to uncomplicated COVID-19 pneumonia.